20. ASSESSMENT OF NUTRITIONAL RISK AND SOME RELATED FACTORS IN MECHANICALLY VENTILATED PATIENTS USING MODIFIED NUTRIC (MNUTRIC) SCORE (Vietnam Journal of Community Medicine, 2024)
Malnutrition affects disease status, increases the risk of infection, increases the length of hospital stay and length of mechanical ventilation and increases the risk of death in critically ill patients. Objectives: Classification the nutritional risk and identification some factors related to treament results in mechanically venticated (MV) patients using the mNUTRIC scale value. Subjects: The study was conducted on 100 patients ≥18 years old and required MV for more 48h at the intensive care unit (ICU) - Nghe An friendship general hospital from march to may, 2023. Methods: Cross-sectional descriptive study. Results: Average age 72.99; male 72%; The high risk of malnutrition according to the mNUTRIC scale accounted for 40% and had an average score of 6.43. The overall mortality rate was 26% and the mortality rate in the mNUTRIC group ≥ 5 was 47.5%. The mean score of mNUTRIC ≥5 in the mortality group was higher than that of mNUTRIC
Keywords: Nutritional risk, Modified-NUTRIC score, Mechanical ventilation.